(untitled) (Research, Society and Development, 2020)
The ceramic materials market is of great importance in various sectors of industry such as construction as it results in the production of bricks, tiles and block, steelmaking and boiler making in the production of bricks and refractory blocks. All these processes for the production of ceramic materials, consume a lot of energy and sometimes do not achieve a perfect porosity, culminating in the change in strength of the final material. This work aims the synthesis of simple ceramic specimens, others coal addition and others with graphite addition, in order to verify the compressive strength in different heat treatments. All were submitted to heat treatment in conventional furnace, having a different process in the graphite specimens, which were submitted to microwave processes, taking advantage of a physical property of energy emission when excited. The addition of charcoal generated significant improvements in porosity and compressive strength, a result that was also observed in the addition of graphite, but more potentiated by passing through the microwave, which caused an improvement in physical properties and a reduction in the time. where the material was in the form and could save energy. This process has been shown to be promising for use in ceramic production plants as it improves physical properties and reduces energy consumption.